A new species of Tupiperla Froehlich, 1969 (Plecoptera: Gripopterygidae) from Serra da Jibóia, Bahia, Brazil - Duarte, Tácio; Bispo, Pitágoras C. [UNESP]; Calor, Adolfo R. (Magnolia Press, 2014)
The gripopterygid genus Tupiperla comprises 18 species, 16 have been recorded from Brazil, including T. guariru n. sp., described here. The new species was collected from streams in the Serra da Jibóia region, Bahia State, Brazil using light traps. Additional material from Amargosa, Bahia State, Brazil was also studied. Copyright © 2014 Magnolia Press.
Keywords: Aquatic Insects; Freshwater; Gripopterygidae; Neotropical; Stoneflies